Otimização de pavimento de lajes nervuradas protendidas - Rosendo Sobrinho, Francisco (2018)
The system of ribbed slabs, with the reduction of concrete in the traction region, besides presenting a more efficient performance, allows to overcome bigger spans, which generates a greater architectural flexibility to the pavement. In addition to the pretension, there is another great advance in the search of an efficient system for the design of pavements of buildings, in particular, the system post-tensioned unbonded tendon. New performance requirements for residential buildings, in particular with regard to sound insulation and fire safety, have raised questions about the economic efficiency of the usual patterns in the form of ribbed slabs. Studies with isolated ribbed slabs in reinforced concrete using cost optimization techniques have shown that new standards must be adopted. The objective of the present proposal is to present a model for the optimization of unidirectional posttensioned ribbed slabs, aiming at minimizing the cost of material including Manpower having as variables the plastic molding pattern, number of struts and cable eccentricity. Commercial standards were evaluated. The constraints of the problem are in relation to the State Limit Last and Service in the structural analysis adopts the model of finite elements of grid. Because it involved discrete variables, a genetic algorithm was used to solve the problem. The solutions obtained were attractive in terms of generating a preliminar solution that can help the designer in the definition of the initial project. A parametric study of the spans was evaluated and a behavior consistent with the design practice was verified.